Philosophy in a New Key: A Study in the Symbolism of Reason, Rite and Art - Langer, Susanne K. 1895-1985 (Cambridge, MA Harvard University Press, 1957)
Susanne K. Langer is perhaps the only aesthetician with a firm grasp of mathematics, in particular symbolic logic. She wrote a book on that subject which is close to being a page-turner. Her prose is crystalline and her wit is as well-aimed as are her closely reasoned arguments. Because of her solid background in logical symbolism, she was able to build on the work of Ernst Cassirer and create the only viable science-based theory of aesthetics that I know of. (Recent books by neural scientists treating art as incidental instinctive behavior are misguided exercises in scientific arrogance, not science-based aesthetics).Her work was buried in the avalanche of anti-science that accompanied the rise of post-modernism, and her wonderful books are no longer in print. This book, along with her masterpiece, "Feeling and Form," work together to create a solid foundation for a rational understanding of how each of the major art forms work to create their powerful effects.Her unfinished magnum opus, "Mind," is fascinating, strange, and worth a careful reading.
Keywords: 20th Century (1901-2000); Philosophy; USA